Particle Swarm Optimization Algorithm Implementation for Multiple Drones Control in Continuous Task Simulation - Oliveira, Nicolas; Moreira, Erick; Rosa, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Robot swarms are an alternative approach that is standing out due to increased processing capacity, improvements in miniaturization, and reduced robot costs. It has led to increased the use of drones in an ever-increasing range of scenarios. This work proposes the development and implementation of a solution tested in simulations that can be replicable in a real flight to plan the path of multiple drones and perform a task continuously. Experiments have shown that the proposed solution proved to be a useful functional tool with the ability to generate a satisfactory and accurate trajectory for robots that detect and avoid collisions in their trajectories by satisfactorily performing an independent robot relay without harming the task.